The Nature of Self-Defense in Draco’s Homicide Law: The Restoration of IG I3 104, lines 33–35 - Harris, Edward M. (Hyperboreus, 2017)
This essay studies the phrase “starting unjust blows” (ἄρχων χειρῶν ἀδίκων) which has been restored in lines 33–35 of Draco’s homicide law (IG I3 104). A careful examination of the phrase shows that it does not come from a statute about homicide, but about a law concerning assault (αἰκείας). The phrase should therefore not be restored in lines 33–35 of Draco’s law. A new edition of the inscription is urgently needed.